2006
DOI: 10.1039/b510071b
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of a DNAzyme into Au-coated nanocapillary array membranes with an internal standard for Pb(ii) sensing

Abstract: A Pb(ii)-specific DNAzyme has been successfully incorporated into Au-coated polycarbonate track-etched (PCTE) nanocapillary array membranes (NCAMs) by thiol-gold immobilization. Incorporation of the DNAzyme into the membrane provides a substrate-bound sensor using a novel internal control methodology for fluorescence-based detection of Pb(ii). A non-cleavable substrate strand, identical to the cleavable DNAzyme substrate strand except the RNA-base is replaced by the corresponding DNA-base, is used for ratiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 43 publications
(52 reference statements)
0
63
0
Order By: Relevance
“…[12,13] Because of reagent depletion along the pores,r educed platingr ates and inhomogeneous deposits are found. [3,4,12,13,33,36] In the case of the template membranes appliedh ere, ar eliable transport of the plating reagents to the inner surfaces is especially difficult due to the dense arrangemento fh igh-aspect-ratio pores. Beside the deposition kinetics, the seeding quality and the morphology of the plated metal films strongly affect the homogeneity and nanostructure of the resulting networks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] Because of reagent depletion along the pores,r educed platingr ates and inhomogeneous deposits are found. [3,4,12,13,33,36] In the case of the template membranes appliedh ere, ar eliable transport of the plating reagents to the inner surfaces is especially difficult due to the dense arrangemento fh igh-aspect-ratio pores. Beside the deposition kinetics, the seeding quality and the morphology of the plated metal films strongly affect the homogeneity and nanostructure of the resulting networks.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to metal deposition, the templates were covered with Ag NPs by sensitizationw ith aS nCl 2 solution,f ollowed by activation with an ammoniac solutiono fA gNO 3 . [37] Pederson mechanistically analyzed this process on glass substrates using X-ray photoelectron spectroscopy and suggested the establishment of af irmly bound layer of Sn II during sensitization.…”
Section: Resultsmentioning
confidence: 99%
“…114 An internal standard was also introduced into the same sensors immobilized on nanocapillary array membranes to realize ratiometric fluorescence detection, which is more resistant to background fluctuation. 115 Later, microfluidic sensor devices for Pb 2+ detection were developed by conjugating the same DNAzymes on polymethylmethacrylate (PMMA) microchannel walls. 116 By immobilizing DNAzymes and substrates on microarrays, Ye’s 117 and Zhao’s 118 groups constructed sensor arrays for high throughput detection of Pb 2+ and Cu 2+ , which combined the high selectivity and sensitivity of DNAzymes and the high throughput analysis of microarrays.…”
Section: Metal Ion-dependent Dnazymes For Metal Ion Recognitionmentioning
confidence: 99%
“…The ability for signal transduction on solid supports has been demonstrated for molecular beacons (Du et al, 2005;Li et al, 2001;Yao and Tan, 2004). It has also been shown that chemical sensors (Basabe-Desmonts et al, 2004), or assays involving third interactants, such as conjugated polymers (Chen et al, 1999;Liu and Bazan, 2005) or DNAzymes (Wernette et al, 2006), can be adapted to work on supports.…”
Section: Microarray Applicationsmentioning
confidence: 97%